Islamic Criticism (Kant & Faruqi's Synthesis): A New Paradigm for Understanding the World in a Whole and Integrated Manner - Mohamad Topan; Rr. S. Murtiningsih; A. H. Utomo (Universitas Darussalam Gontor, 2026)
Modernity faces a crisis of meaning marked by the fragmentation of knowledge and the separation of facts from values. This article responds to this by presenting a visionary synthesis between Immanuel Kant's critical epistemology from the Western tradition and Ismail Raji Al-Faruqi's project of Islamizing knowledge. Kant, with his distinction between phenomena-noumena, reminds us of the limits of human reason, which can only reach the empirical world. Meanwhile, Al-Faruqi offers the Tawhid paradigm as an integrative principle that combines revelation, reason, and sensory experience. Through a comparative-hermeneutical analysis, this research develops the framework of